INTEGRATION OF HUMAN RESOURCE MANAGEMENT TO MINIMIZE CORE EMPLOYEE TURNOVER AT COFFEE SHOP - Aidil Ghufran Rasyid; Harmein Nasution (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The coffee shop industry faces the challenge of high employee turnover intentions that can affect operational stability and service quality. This study aims to analyze human resource (HR) management practices implemented at Coffee Shop X, identify the dominant factors causing employee turnover intentions, and formulate an integrated HR management system through benchmarking with Coffee Shop Y. The study used a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, observation, and documentation. The results of the study indicate that Coffee Shop X has implemented a formal HR management system based on SOPs and KPIs, covering recruitment, training, performance appraisals, compensation, and termination of employment. However, turnover intentions still arise due to workload pressure during peak hours, limited compensation, and the need to strengthen the continuous evaluation and employee development system. Benchmarking with Coffee Shop Y shows that the implementation of continuous performance assessments, direct communication, and a disciplined and adaptive work culture can improve performance consistency and employee retention. Integration of these best practices is recommended to strengthen Coffee Shop X's HR system and reduce employee turnover intentions sustainably.